PENGARUH PENGGUNAAN MEDIA WAYANG GOLEK TERHADAP KEMAMPUAN BERCERITA PADA SISWA KELAS 5 SEKOLAH DASAR - Rochima Fauqa Muamalah; Mega Desi Ambarwati; Muhammad Fauzi; Ishmatun Naila (Universitas Muhammadiyah Surabaya, 2022)
Humans are social creatures who need communication and interaction with fellow living things. The ability to communicate is very necessary because it can increase trust, good relations, and prevent a problem. If the communication skills are good, of course the language skills that someone has are also good. The research, entitled The Effect of using wayang golek media on storytelling skills in grade 5 elementary school students is a quantitative study. Quantitative research is research based on the philosophy of positivism, used to examine the population or sample according to Sugiono. This study uses Pre Experimental with the type of One Group Pretest Posttest Design. Based on the results of the normality of the SPSS data analysis with the Kolmogorov-Smirnov Test with the Kolmogorov-Smirnov Â Z of 0.93 and Asymp. Sig. (2-tailed) of 0.34 greater than 0.05 (0.34 > 0.05). So it can be concluded that the data obtained are normally distributed. In the homogeneity test, the results of the pretest and posttest were 0.768. Because the value of sig. 0.768 > 0.05, it can be concluded that the data variance is homogeneous. that there is a difference between before and after treatment. Because: p value < 0.05 (95% confidence). Mean: -0.6. Negative value: This means that there is a tendency for differences after treatment. So it can be stated that there is an effect of the use of wayang golek on the use of wayang golek on the storytelling ability of elementary school students.Â Keywords puppet show; storytelling ability